Role of MicroRNAs in Hepatic Fibrosis Progression - Devaraj Ezhilarasan (Journal of Applied Pharmaceutical Science, 2018)
Acute liver injury induced deviation in liver architecture are transient and often reversible. While chronic liver diseases lead to progressive net accumulation of extracellular matrix (ECM) in the liver leading to hepatic fibrosis. If hepatic fibrosis is untreated, hepatic fibrosis can lead to cirrhosis and consequence of organ failure and death. Hepatic stellate cells (HSCs) activation plays a significant role in the pathogenesis of hepatic fibrosis. MicroRNAs are short, non-coding, single-stranded RNA and their modulation upon chronic liver injury are said to involve in the activation and proliferation of HSCs that causes synthesis and accumulation of the enormous amount of ECM proteins by HSCs in liver hepatic fibrosis consequently. This review summarizes the modulation of key miRNAs pertaining to hepatic fibrosis.
Keywords: Hepatic stellate cells,extracellular matrix,miRNAs,liver fibrosis.